1998
DOI: 10.1200/jco.1998.16.12.3810
|View full text |Cite
|
Sign up to set email alerts
|

BEACOPP, a new dose-escalated and accelerated regimen, is at least as effective as COPP/ABVD in patients with advanced-stage Hodgkin's lymphoma: interim report from a trial of the German Hodgkin's Lymphoma Study Group.

Abstract: Combined with local irradiation, BEACOPP in one or both variants shows superior disease control compared with COPP/ABVD, with acceptable acute toxicity. Further follow-up is required to assess the effect of dosage and the effect on survival and late toxicities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
100
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(103 citation statements)
references
References 25 publications
0
100
0
3
Order By: Relevance
“…The intensive regimen of bleomycin, etoposide, doxorubicin, cyclophosphamide, vincristine, and prednisone (BEACOP) has been proposed as a very effective induction treatment for patients with high-risk HL. 46 However, it has not been demonstrated that salvage regimens are as feasible or as effective after BEACOP as they are after less intensive, conventional regimens. To address this issue, a randomized trial of ABVD compared with BEACOP, both coupled with an HDS-like salvage program, in patients who do not respond to induction therapy is underway at IIL centers.…”
Section: Discussionmentioning
confidence: 99%
“…The intensive regimen of bleomycin, etoposide, doxorubicin, cyclophosphamide, vincristine, and prednisone (BEACOP) has been proposed as a very effective induction treatment for patients with high-risk HL. 46 However, it has not been demonstrated that salvage regimens are as feasible or as effective after BEACOP as they are after less intensive, conventional regimens. To address this issue, a randomized trial of ABVD compared with BEACOP, both coupled with an HDS-like salvage program, in patients who do not respond to induction therapy is underway at IIL centers.…”
Section: Discussionmentioning
confidence: 99%
“…29,33 Very few HL patients with advanced disease and high-risk features received BEACOPP chemotherapy (bleomycin, etoposide, doxorubicin, cyclophosphamide, vincristine, procarbazine, prednisone) during the study period. 2,34 Combined modality treatment for patients with limited-stage disease became increasingly common during the 1980s. 35 Irradiation for previously bulky disease in patients with stage III-IV disease was also widespread during the 1980s and 1990s.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Once patients relapse after initial therapy, however, conventionaldose chemotherapy regimens usually fail to provide durable complete remissions. [17][18][19][20][21][22][23][24] In the series with the longest follow-up, Longo and associates 17 reported that although 93% of relapsing patients could be re-induced into a second complete remission, only 17% of these remissions were durable.…”
mentioning
confidence: 99%